Conceptualising Primary-Secondary School Transitions: A Systematic Mapping Review of Worldviews, Theories and Frameworks - Jindal-Snape, Divya; Symonds, Jennifer E.; Hannah, Elizabeth F. S.; Barlow, William (Frontiers in Education, 2021)
Abstract There is continued interest internationally in primary-secondary school transitions. Fourteen literature reviews of primary-secondary transitions have been published over the last 20 years, however none of them have systematically analysed primary-secondary school transition ontology, i.e. researchers’ worldviews, theories/models and frameworks. This is a major gap in these reviews and the papers published in this area; this is of concern as it is difficult to trust the robustness of a study if its foundation, such as researchers’ conceptualisation of transitions, is not visible. Therefore, using the Evidence for Policy and Practice Information and Co-ordinating Centre (EPPI-Centre) approach, we undertook a systematic mapping review, of empirical studies published internationally between 2008 and 2018. Our objectives were to explore researchers’ and research participants’ conceptualisation of transitions, the conceptual framework used by the researchers and their discourse about transitions. Of the 96 studies included in this systematic mapping review, most had not clearly defined transition, and even when conceptualisation was explicit, it did not underline the research design or frame the findings. Most researchers adopted previously used theoretical frameworks. These theoretical frameworks can be beneficial; however, as the researchers did not adapt or develop them in the context of transitions research, it limits a meta-theoretical understanding of transition research. it limits a meta-theory/world view of transitions as they did not adapt or develop them in the context of transitions research. Further, the majority did not report study participants’ conceptualisation of transitions. Similarly, a large number of researchers adopted a negative discourse about primary-secondary school transitions, with some using a mixed discourse and only two papers had a primarily positive discourse. This systematic mapping review is original and significant as it is the first study to provide a review of school transitions ontology and offers unique insights into the conceptual and methodological gaps that international transitions researchers should address. Keywords: Primary school, secondary school, transitions, conceptualisation, discourse, theory, systematic literature review, systematic mapping review, ontology